Observational Study of Diaphyseal Nutrient Foramina in Fully Ossified Dry Human Left Tibia (Bangladesh Journal of Anatomy, 2016)
Context :Nutrient foramen is an opening through which the nutrient artery enters and supplies the shaft of the long bones. An understanding of the number and location of diaphyseal nutrient foramina on tibia is very important clinically, especially for orthopedic and vascular surgeons as well as to radiologists for planning of treatment. Materials and methods : This is an observational descriptive type of study which was carried out in the department of Anatomy of Sir Salimullah Medical College (SSMC),Dhaka from July 2014 to June 2015 performed on two hundred (n=200; male=102 & female=98) fully ossified dry human left tibia.This study was carried out on the samples by direct observational method. Results: The nutrient foramen was single in number in 99% samples , double in number in 1 % samples. The location of nutrient foramen was observed on the posterior surface in 97.5% cases and on the antero-lateral surface in 2.5% cases. No nutrient foramen was observed on the antero medial surface. Conclusion: The anatomical knowledge gained from this study and the obtained recorded data can be useful in certain surgical procedures as well as bone transplant, reconstruction surgery, tumor resection and microvascular surgery.Bangladesh Journal of Anatomy July 2016, Vol. 14, No. 2 pp. 39-42